731 Who is most at risk for nightmares? Demographic and psychosocial differences in nightmare prevalence among nurses. (3rd May 2021) - Martinez, Jaylin; Santiago, Bianca; Slavish, Danica; Dietch, Jessica; Messman, Brett; Kelly, Kimberly; Ruggero, Camilo; Taylor, Daniel
Abstract: Introduction: Nurses are subject to stressful work environments, which may negatively impact their sleep and increase their risk for nightmares. Previous studies have shown that women, night shift workers, and individuals with comorbid psychological conditions are more likely to report nightmares. Yet no studies have comprehensively examined demographic and psychosocial factors of nightmares among nurses. Methods: To address this gap, we examined demographic (age, gender, race, ethnicity, number of children, marital status, shift work status) and psychosocial (chronotype, PTSD, anxiety, depression, perceived stress) correlates of nightmares in a sample of 462 nurses (91% female; mean age = 39.03, SD = 11.07; 78% White; 10% Hispanic/Latinx). Nightmares were determined two ways: 1) using a newly validated retrospective survey measure, the Nightmare Disorder Index (NDI), and 2) using aggregated prospective reports of daily nightmare frequency across 2 weeks (nurses who reported any nightmares in the past 2 weeks were classified as having nightmares). Results: Nurses experiencing nightmares as determined by the NDI (n = 236; 51%) were younger, more likely to be female, less likely to have children, more likely to be an intermediate chronotype, less likely to be a morning chronotype, and had higher mean levels of PTSD, anxiety, depression, and perceived stress than nurses without nightmares. Nurses experiencing nightmares as determined by daily surveys (n = 191; 41%) were not different in terms of any demographic characteristics, but had higher levels of PTSD, anxiety, depression, and perceived stress than those nurses without nightmares. Conclusion: Demographic and psychosocial differences in nightmare prevalence may differ based on how nightmares are assessed (i.e., retrospective vs. prospective measures). Overall, nurses with higher stress, PTSD, depression, and anxiety may be at greatest risk of having nightmares. Future studies should examine if targeting these factors results in improvements in sleep and well-being among nurses. Support (if any): NIH/NIAID R01AI128359-01